Landscapes - Johnson, Sarah, 1980 February 16- (Themes in environmental history ;, 2010)
Comprising essays selected from 'Environment and History' and 'Environmental Values', the inexpensive volumes in this series address important aspects of environmental history through theoretical essays and case studies. Landscapes explores the conceptualisation of environments as landscape, philosophically and historically.